Prevalence of anaemia amongst adolescents attending OPD at rural health and training centre, Era’s Lucknow Medical College and Hospital - Ahmad, Sumaiya; Gupta, Pratibha; Khatoon, Ruby; Zaidi, Zeashan Haider; Sahai, Raghunath (International Journal Of Community Medicine And Public Health, 2018)
Background: Nutritional anemia is worldwide problem with highest prevalence in developing countries. Causes of anemia are inadequate intake and poor absorption of iron, malaria, hookworm infestation, diarrhea, heavy menstrual blood flow etc. It involves population of all age group and sex. But adolescent are more vulnerable to it. The objective of the study was to find prevalence of anemia amongst adolescents attending rural health and training Centre of Era’s Lucknow Medical College and Hospital. Methods: This cross-sectional study was carried out in the Rural Health Training Centre (RHTC), Era’s Lucknow Medical College. All the adolescents attending OPD at RHTC for any health problem were included in the study. Study period was about one year i.e. from November 2016 to October 2017. Blood sample was collected for hemoglobin estimation. Hemoglobin estimation was done by Sahli’s hemoglobinometer. Hb criteria were taken according to WHO standard. Results: The overall prevalence of anemia was 55.1 % for both males and females. 64.7% of the females and 32.5 % of the males were anemic. The proportion of mild anemia was 55.6% (53.9% in females and 68.1% in males), moderate anemia was 33% (35.2% in females and 25% in males) and severe anemia was 11.2% (10.7% in females and 6.8% in males). Conclusions: Anaemia was significantly higher in females in comparison to males in moderate and severe category. There is need to develop strategies for intensive adult education, nutrition education and dietary supplementation and anemia prophylaxis.